Clinical review: Post-extubation laryngeal edema and extubation failure in critically ill adult patients - Wittekamp, Bastiaan HJ (BioMed Central, 2009)
Laryngeal edema is a frequent complication of intubation. It often presents shortly after extubation as post-extubation stridor and results from damage to the mucosa of the larynx. Mucosal damage is caused by pressure and ischemia resulting in an inflammatory response. Laryngeal edema may compromise the airway necessitating reintubation. Several studies show that a positive cuff leak test combined with the presence of risk factors can identify patients with increased risk for laryngeal edema. Meta-analyses show that pre-emptive administration of a multiple-dose regimen of glucocorticosteroids can reduce the incidence of laryngeal edema and subsequent reintubation. If post-extubation edema occurs this may necessitate medical intervention. Parenteral administration of corticosteroids, epinephrine nebulization and inhalation of a helium/oxygen mixture are potentially effective, although this has not been confirmed by randomized controlled trials. The use of non-invasive positive pressure ventilation is not indicated since this will delay reintubation. Reintubation should be considered early after onset of laryngeal edema to adequately secure an airway. Reintubation leads to increased cost, morbidity and mortality.